P17, an Original Host Defense Peptide from Ant Venom, Promotes Antifungal Activities of Macrophages through the Induction of C-Type Lectin Receptors Dependent on LTB4-Mediated PPARγ Activation - Benmoussa, Khaddouj; Authier, Hélène; Prat, Mélissa; AlaEddine, Mohammad; Lefèvre, Lise; Rahabi, Mouna Chirine; Bernad, José; Aubouy, Agnès; Bonnafé, Elsa; Leprince, Jérome; Pipy, Bernard; Treilhou, Michel; et al. (Frontiers in Immunology, 2017)
Despite the growing knowledge with regard to the immunomodulatory properties of host defense peptides (HDPs), their impact on macrophage differentiation and on its associated microbicidal functions is still poorly understood. Here, we demonstrated that the P17, a new cationic antimicrobial peptide from ant venom, induces an alternative phenotype of human monocytes-derived macrophages (h-MDMs). This phenotype is characterized by a C-type lectin receptors (CLRs) signature composed of mannose receptor (MR) and Dectin-1 expression. Concomitantly, this activation is associated to an inflammatory profile characterized by reactive oxygen species (ROS), IL-1β and TNF-α release. P17-activated h-MDMs exhibit an improved capacity to recognize and to engulf C. albicans through the overexpression both of MR and Dectin-1. This upregulation requires arachidonic acid (AA) mobilization and the activation of PPARγ nuclear receptor through the leukotriene B4 (LTB4) production. AA/LTB4/PPARγ/Dectin-1-MR signaling pathway is crucial for P17-mediated antifungal activity of h-MDMs, as indicated by the fact that the activation of this axis by P17 triggered ROS production and inflammasome-dependent IL-1β release. Moreover, we showed that the increased antifungal immune response of h-MDMs by P17 was dependent on intracellular calcium mobilization triggered by the interaction of P17 with pertussis toxin-sensitive G protein coupled receptors on h-MDMs. Finally, we also demonstrated that P17-treated mice infected with C. albicans develop less severe gastrointestinal infection related to a higher efficiency of their macrophages to engulf Candida, to produce ROS and IL-1β and to kill the yeasts. Altogether, these results identify P17 as an original activator of the fungicidal response of macrophages that acts upstream PPARγ/CLRs axis and offer new immunomodulatory therapeutic perspectives in the field of infectious diseases.